‘Running Riot’: Violence and British Punk Communities, 1975-1984 - Andrew H. Carroll (Criminocorpus, 2019)
Roused by their experience at the Notting Hill Carnival of 1976, the Clash penned their first single “White Riot” and at an early stage helped to establish the burgeoning punk community’s obsession with violence. In the context of the social and economic crises of the late 1970s and early 1980s, street level disorders and attacks were common place. However, punk’s use of aggression was more than a simple embrace of violence’s banality during the period. It constituted a response to postwar British discourse about youth and the stark rise in divorce rates. Punks used violence to react against cultural isolation and to find individual, masculine empowerment as part of a subcultural community.